Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have been told multiple times that the logarithmic function is the inverse of the exponential function and vice versa. My question is; what are the implications of this? How can we see that they're the inverse of each other in basic math (so their graphed functions, derivatives, etc.)?

share|improve this question
1  
They are inverse in the sense that $\log_a(a^b) = b$. For $a = e$, you have the natural logarithm, $\ln(e^b) = b$. –  Pål GD Jan 15 '13 at 13:59

3 Answers 3

It means that $e^x$ is a bijection from $\Bbb R$ onto $(0\infty)$, and that $\ln(x)$ is a bijection of $(0,\infty)$ onto $\Bbb R$. This means both functions pair up points in their domain and range: roughly speaking, "nothing is left out", and "no two pairs overlap".

The inverse properties say that: $e^{\ln(x)}=x$ for all $x\in (0,\infty)$ and $\ln(e^x)=x$ for all $x\in \Bbb R$. These properties are useful for solving equations, for one thing. If you see $e^x=4$, then by applying $\ln$ to both sides:

$$ \ln(e^x)=\ln(4) $$ and by that cancellation, the left hand side is just $x$, so it is now solved for $x$.

Graphically you can check that they are inverses. If you graph both $e^x$ and $\ln(x)$ on the same axes, then you will observe that they are reflections of each other across the line $y=x$. This is the case for all pairs of mutually inverse functions.

That graphical reflection translates, in symbols, to: if $(x_0,y_0)$ is on the graph of $e^x$, that means $e^x$ sends $x_0$ to $y_0$. Since the functions are inverses, that means $\ln(x)$ sends $y_0$ to $x_0$. Therefore, $(y_0,x_0)$ is on the graph of $\ln(x)$. The act of switching the coordinates of the ordered pairs produces the reflection across $y=x$.

There is one relationship you can derive about the derivatives. Since $f(f^{-1}(x))=x$, differentiating both sides (using the chain rule on the left) says that $f'(f^{-1}(x))\cdot (f^{-1})'(x)=1$. Solving for $(f^{-1})'(x)$ you get that:

$$ (f^{-1})'(x)=\frac{1}{f'(f^{-1}(x))} $$

Using $f(x)=e^x$ and knowing that $f'=f$ for this function, you get:

$$ \frac{d\ln(x)}{dx}=\frac{1}{e^{\ln(x)}}=\frac{1}{x} $$

There are a lot of details and rigor I have not mentioned, but I hope this gives you a bit of a flavor of what is going on. Don't use this as an excuse not to look at your text!


PS: I interpreted "the exponential" to mean $f(x)=e^x$, but of course everything above (with some care, especially in the case of the derivative) can be changed over to the case of $f(x)=a^x$ and $f^{-1}(x)=\log_a(x)$

share|improve this answer

Actually the logarithm function is defined as the inverse of exponent function. It's not a property of these functions, it's how the logarithm is introduced.

If $a^b=c$ then the power by which you raise a to obtain c is the logarithm: $b=log_a c$.

share|improve this answer
1  
That's the case in some developments. There are also texts that start by defining $\log x = \int_1^x \frac 1x\,dx$ and then define $\exp(x)$ as the alternative of the logarithm. Yet other developments define the logarithm and the exponential separately and then have to prove explicitly that they are inverses. –  Henning Makholm Jan 15 '13 at 15:10

Just to generalize:

A function $g: Y \to X$ is an inverse function of $\;f: X \to Y\;$ (and vice versa) if and only if $$\;g \circ f = id_X\; \text { and}\;\,f\circ g = id_Y:\;$$ that is, if and only if $\;g(f(x)) = x\;$ for all $x \in X$ and $\;f(g(y)) = y\,$ for all $\,y \in Y$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.